2012
DOI: 10.4103/1742-6413.94518
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a protocol for immunocytochemical staining and chromogenicin situhybridization of Giemsa and Diff-Quick prestained cytological smears

Abstract: Background:Protocols for immunocytochemical staining (ICC) andin situhybridization (ISH) of air-dried Diff-Quick or May-Grünwald Giemsa (MGG)-stained smears have been difficult to establish. An increasing need to be able to use prestained slides for ICC and ISH in specific cases led to this study, aiming at finding a robust protocol for both methods.Materials and Methods: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 24 publications
(12 reference statements)
0
21
1
Order By: Relevance
“…According to the ROSE concept (Rapid On‐Site Evaluation), cytologic examination is a valuable tool for establishing a definitive tissue diagnosis in practice and can complement histologic studies by revealing previously unrecognized features . There is, however, an enormous demand for more specific diagnoses to confirm or specify atypical and rare infections or undifferentiated neoplasia .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the ROSE concept (Rapid On‐Site Evaluation), cytologic examination is a valuable tool for establishing a definitive tissue diagnosis in practice and can complement histologic studies by revealing previously unrecognized features . There is, however, an enormous demand for more specific diagnoses to confirm or specify atypical and rare infections or undifferentiated neoplasia .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies and case reports have demonstrated the feasibility of subjecting cytologic, histologic, and histochemically stained slides, and immunocytochemistry and in situ hybridization procedures, to second analyses . These studies were mainly carried out after the removal of previous dyes by alcohol, bleaching with hydrogen chloride, or applying MWTs in citrate buffer and distilled water …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations